Synthesis of Fe-Salen-MCM-41 hybrid catalysts / Syuhada Mohd Tahir ... [et al.] - Mohd Tahir, Syuhada; Hamdan, Halimaton; Mohd Tahir, Syahidah; Mohd Tahir, Mariya (2013)
MCM-41 with SiO2/AI203 ratios =60 were used as a support for heterogenization of Fe (III) salen complex to form hybrid catalysts. Flexible ligand method was applied for immobilization of complex onto the supports. The physical properties of these hybrid catalysts were characterized using XRD, FTIR, UV-Vis DR, EDX and BET. The powder XRD data confirmed that the structural order of MCM-41 remained intact after the encapsulation process. FTIR and EDX studies show the presence of Fe (III) in the hybrid catalyst sample. UV-Vis DR analysis reveals that the free and encapsulated complexes exhibit the tetrahedral geometry. BET results show that the pore volumes of the synthesized hybrid catalysts are lower than the neat MCM-41. thus proved successful encapsulation.